Pig farming in Haryana : Prospects and retrospects - PANDAY, U K; SINGH, M P; RAM, MANGE (The Indian Journal of Animal Sciences, 2013)
Landless as well as landholders of different caste strata have adopted the piggery enterprise under different management and conditions in Haryana. Sows mostly farrowed twice, average litter size ranged between 7 and 8, the mortality in young pigs ( below 2 months) ranged between 10 and 21%, while amongst pigs above 2 months about 6%. The major constraints inhibiting the development of piggery enterprise in the state are lack of proper market infrastructures, institutional loans, balanced and subsidized feed and veterinary health care. Housing conditions did not meet the prescribed standards and insanitary conditions prevailed in the sheds. spacing was not proper (either overeowded or over spacious) lacked in proper orientation. Heavy losses ofpiggery unit were also observed due non-adoption of livestock insurance cheme. The initial capital investments per pig ranged between Rs I 855 and 3 327 amongst farms utilizing hotel waste for feeding while between 2 539 and 3 254 amongst farms not using hotel waste. The share of feed into the total working cost in different categories of piggery farms utilizing hotel wastes ranged from 45 to 67% and those not utilizing hotel wastes from 50 to 66%. The labour cost ranged from 7 to 22% in piggery farms feeding with hotel wastes while between 22 and 36% farms feeding with hotel wastes while 22% and 36% amongst without hotel wastes. The annual net returns/pig ranged between Rs 908 and 1 136 on farms rearing pigs with hotel wastes. Amongst specified variables, both the annual feed and labour cost/pig had the negative but significant relationship with the annual net income over working expenses/pig.